PHLDA2 is an imprinted gene in cattle - Sikora, K. M.; Magee, D. A.; Berkowicz, E. W.; Lonergan, P.; Evans, A. C. O.; Carter, F.; Comte, A.; Waters, S. M.; MacHugh, D. E.; Spillane, C. (Animal genetics, 2012)
Summary Genomic imprinting is an epigenetic non‐Mendelian phenomenon found predominantly in placental mammals. Imprinted genes display differential expression in the offspring depending on whether the gene is maternally or paternally inherited. Currently, some 100 imprinted genes have been reported in mammals, and while some of these genes are imprinted across most mammalian species, others have been shown to be imprinted in only a few species. The PHLDA2 gene that codes for a pleckstrin homology‐like domain, family A (member 2), protein has to date been shown to be a maternally expressed imprinted gene in humans, mice and pigs. Genes subject to imprinting can have major effects on mammalian growth, development and disease. For instance, disruption of imprinted genes can lead to aberrant growth syndromes in cloned domestic mammals, and it has been demonstrated that PHLDA2 mRNA expression levels are aberrant in the placenta of somatic clones of cattle. In this study, we demonstrate that PHLDA2 is expressed across a range of cattle foetal tissues and stages and provide the first evidence that PHLDA2 is a monoallelically expressed imprinted gene in cattle foetal tissues, and also in the bovine placenta.